A SURVEY PAPER ON ELASTIC SEARCH SIMILARITY ALGORITHM - Nath, Nilanjana Dev; Jha, Shreekant; M, Janki Meena; S.p, Syedibrahim (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Elasticsearch is a web search tool in view of Lucene. Apache Lucene is a free and open-source data retrieval programming library. Versatile Search gives a conveyed, multitenant-fit full-content web search tool with a HTTP web interface and pattern free JSON archives. It is created in Java and has been released as open source under the terms of the Apache License. Elasticsearch can be utilized to pursuit a wide range of records. It gives adaptable hunt, has close continuous pursuit, and backings multitenancy. It is appropriated, which implies that records can be partitioned into shards and every shard can have zero or more duplicates. Every hub has one or more shards, and goes about as a facilitator to delegate operations to the right shard(s). Elasticsearch is like a wrapper on top of Lucene. In this paper a detailed description of how lucene's scoring algorithm works and how elasticsearch uses it as similarity algorithmâ€